"I'd like to order with a server." an experimental study of restaurant menu performance. Issue 7 (2nd July 2020) - Leung, Xi Y.; Josiam, Bharath M.; Moody, Bailey M.
ABSTRACT: The Asia Pacific region has the largest market in the foodservice industry. This study aims to explore the performance of self-service tablets in comparison with traditional paper menus. A field experiment was conducted in a casual dining restaurant. The results show that self-service tablets had better design whereas paper menus had better communication feature. Paper menus elicited better responses than self-service tablets. The study highlighted the technological pause phenomenon and the importance of human contact in the restaurant industry. The implications of this study are applicable to restaurant operators in the Asia Pacific region, especially to those targeting foreign visitors.